2023
DOI: 10.1002/jtr.2601
|View full text |Cite
|
Sign up to set email alerts
|

Creative tourism and visitor motivation

Pierce Qiang Li,
Jason F. Kovacs

Abstract: Creative tourism has been explained as a new genre of tourism that offers the visitor an opportunity to develop their creative potential through an engaged experience in the destination visited. Despite a growing literature on the topic, little attention has been given to examining what motivates creative tourists to visit particular places and events. This paper aims to address this research gap by applying the push‐pull framework to investigate the travel motivations of creative tourists. To do so, the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
(169 reference statements)
0
1
0
Order By: Relevance
“…As per the discoveries presented by Figueroa et al (2018), the attraction of international tourists hinges on optimizing tourist influxes, encompassing cultural richness, activities, and natural assets. Studies have indicated that visitors are more inclined towards renowned locations with elevated historical, cultural, creative, food tourism, and aesthetic worth (Li & Kovacs, 2023;Muštra et al, 2023;Seongseop et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As per the discoveries presented by Figueroa et al (2018), the attraction of international tourists hinges on optimizing tourist influxes, encompassing cultural richness, activities, and natural assets. Studies have indicated that visitors are more inclined towards renowned locations with elevated historical, cultural, creative, food tourism, and aesthetic worth (Li & Kovacs, 2023;Muštra et al, 2023;Seongseop et al, 2021).…”
Section: Introductionmentioning
confidence: 99%